Silencing of hypoxia-inducible factor-1β induces anti-tumor effects in hepatoma cell lines under tumor hypoxia. - Sung Hoon Choi; Ae Ri Chung; Wonseok Kang; Jun Yong Park; Mi Sol Lee; Shin Won Hwang; Do Young Kim; Seung Up Kim; Sang Hoon Ahn; Seungtaek Kim; Kwang-Hyub Han (PLoS ONE)
Dimerization of hypoxia-inducible factor-1 beta (HIF-1β) [aryl hydrocarbon receptor nuclear translocator (ARNT)] with HIF-1α is involved in various aspects of cancer biology, including proliferation and survival under hypoxic conditions. We investigated the in vitro mechanism by which silencing of HIF-1β leads to the suppression of tumor cell growth and cellular functions. Various hepatocellular carcinoma (HCC) cell lines (Huh-7, Hep3B, and HepG2) were transfected with small interfering RNA (siRNA) against HIF-1β (siHIF-1β) and cultured under hypoxic conditions (1% O2 for 24 h). The expression levels of HIF-1β, HIF-1α, and growth factors were examined by immunoblotting. Tumor growth was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, and tumor activity was measured by terminal deoxynucleotidyl transferase dUTP nick end labeling, tumor cell invasion, and migration assays. Under hypoxic conditions, silencing of HIF-1β expression suppressed tumor cell growth and regulated the expression of tumor growth-related factors, such as vascular endothelial growth factor, epidermal growth factor, and hepatocyte growth factor. Suppression of tumor cell invasion and migration was also demonstrated in HIF-1β-silenced HCC cell lines. Silencing of HIF-1β expression may induce anti-tumor effects under hypoxic conditions in HCC cell lines.